Пиранья. Охота на олигарха: [роман] / Александр Бушков - Бушков Александр Александрович (ОЛМА Медиа Групп, 2011)
Экземпляры: ф7 (20180112) / Инвентарный номер: 55225 / Цена: 70.00 / Сис.шифр: Р2 / Авт.знак: Б 94 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6